Integrated control of the Stomoxys calcitrans fly in the oil palm cultivation (Elaeis guineensis Jacq) (Revista Sistemas de Producción Agroecológicos, 2013)
The mass production of fresh rachis palm crops (Elaeis guineensis Jacq) generated the biological development opportunity fly stables (Stomoxys calcitrans), increased the population of this blood-sucking insect, affecting livestock in the region, Villanueva (Casanare). To determine the population dynamics of this fly on rachis mounds arranged in field testing was performed for which selected lots were called: F 15, F 16, F 17, F 18, E 20, E 21, E 22 and E 23, considering the proximity to the rachis collection site to promote the presence of stable fly. The distribution of the batch treatments was randomized complete block. According to the results if there was an effect of covering the spine with tents made of tarps on the fly populations. Treatments 20, 25 and 30 days without Spalangia sp. tent were those with a higher biological development of the stable fly Spalangia sp. parasitism of pupae stable fly, fell 16.35% of the population, demonstrating the importance of releases of this parasitoid, ratifying the need to maintain established populations in the field, for eventual management of rachis with canvas tents, as a component within the coating technique. It was also noted that there is a factor of 41% natural mortality of stable fly pupal stage in field.
Keywords: Hematophagous fly; oil palm